2015
DOI: 10.15446/dyna.v82n190.46256
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric corrosivity in Bogota as a very high-altitude metropolis questions international standards

Abstract: <p>This paper presents the first systematic atmospheric corrosion assessment in Bogota. Main facts about the study are related with special characteristics of the City, such as population (more than eight million inhabitants), and altitude (2600 m over the sea level). Relative humidity, temperature, and SO2 concentration were measured. Simultaneously, corrosion rate of AIS/SAE 1006 plain steel was measured along one year. Results show that atmospheric corrosion is between C<sub>2</sub> – C<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…Conversely, site 1 in this study manifests a corrosion rate positioned at a midpoint, comparable with other sites as Hanoi (Vietnam) [ 26 ]. Sites 2 and 5 exhibit corrosion rates at the lower end of the spectrum reported for such atmospheres; however, it is worth noting that these values have also been reported by other authors [ 6 , [27] , [28] , [29] ].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Conversely, site 1 in this study manifests a corrosion rate positioned at a midpoint, comparable with other sites as Hanoi (Vietnam) [ 26 ]. Sites 2 and 5 exhibit corrosion rates at the lower end of the spectrum reported for such atmospheres; however, it is worth noting that these values have also been reported by other authors [ 6 , [27] , [28] , [29] ].…”
Section: Resultssupporting
confidence: 83%
“…6 ). It is noteworthy that all these sites fall within the classification of urban or industrial-urban atmospheres [ 6 , [23] , [24] , [25] , [26] , [27] , [28] , [29] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…A former research reported that atmospheric corrosion of carbon steel in Bogotá was less than 50 μm yr -1 (400 g m -2 yr -1 ) according to meteorological parameters and pollutant concentration data collected by the city network of environmental assessment during several years, and there was mass loss of carbon steel after one year of exposure (Ríos Rojas et al, 2015). Nevertheless, a damage function of carbon steel corrosion from measurements of standard specimens was not found.…”
Section: Sitementioning
confidence: 99%
“…Major salinity differences may also exist between the shores of one side of a country and the other side as each region varies in terms of its characteristics pertaining to the corrosion behaviour of materials. [ 7 ] In Mexico, for example, the corrosion rate for the northern coast is 362.4 µm annum −1 (µm a –1 ), which is significantly higher than the corrosion rate of 91.3 µm a –1 obtained for the southern coast. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%